Understanding ecosystem responses to recurrent marine heatwaves - Emily Lester; Stanley Mastrantonis; Sharyn M. Hickey; Anna Lafratta; Jessica A. Benthuysen; Eben Afrifa-Yamoah; Arani Chandrapavan; Martial Depczynski; Richard D. Evans; David V. Fairclough; Christopher J. Fulton; Marthe Monique Gagnon; et al. (Biological Conservation, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Deciphering the footprints of predator–prey interactions on coral reefs: seasonal dynamics and environmental drivers of reef halos - Emily K. Lester; Michael V.W. Cuttler; Tim J. Langlois; Elizabeth M.P. Madin (Coral Reefs, 2025)
Landscape-scale footprints of behavioural interactions between predators and prey can offer a window into the ecological dynamics of entire ecosystems. In coral reefs, a promising example of this phenomenon includes reef halos, which are bare patches of sand surrounding patch reefs. Reef halos form where the presence of predators restricts herbivory and other foraging activities to close proximity of shelter. Additionally, reef halos persist from year-to-year, are more prevalent in reefs with ostensibly intact predator populations, and are easily measured using satellite imagery. However, the stability of reef halos over short-term (i.e. monthly) scales and how they respond to environmental factors, has yet to be rigorously explored in coral reefs. Here, we used a remote sensing approach to investigate the magnitude of reef halo size fluctuations over time in the Ningaloo Reef, Western Australia, relative to a suite of environmental factors. Although reef halos appear to be a permanent feature of the seascape, the size of individual reef halos fluctuated widely over monthly scales, declining as sea surface temperature and regional upwelling (a proxy for nutrient delivery) increased. We did not find a relationship between halo prevalence and management zone, fish biomass, or patch reef area, which is inconsistent with studies of reef halo formation in other locations. Unravelling this discrepancy with the broader literature will require an in situ experimental approach. Overall, our results demonstrate that single snapshots in time of reef halo size may not be sufficient to yield accurate signals regarding interactions between predators, herbivores, and vegetation.

Love bites? Pre-copulatory behaviours of whale sharks (Rhincodon typus) at Ningaloo Reef, Western Australia - Christine Barry; Emily Lester; Micheal P. Doane; Luciana C. Ferreira; Michele Thums; Adrian C. Gleiss; Mark G. Meekan (Frontiers in Marine Science, 2025)
Very little is known about the reproductive behaviours of whale sharks ( Rhincodon typus ). Here, we describe field observations of courtship behaviour by a whale shark at Ningaloo Reef, Western Australia. We witnessed and recorded following and biting behaviours by a sexually mature male of a smaller female. Following and biting are common events during courtship and copulation of other species of elasmobranchs. Our observations are consistent with earlier reports of courting behaviours in whale sharks provided by fishers, the pilot of a light plane and observations of courtship by a sexually mature male towards females held in aquaria.

Citizen science highlights rare behaviours by the spotted eagle ray Aetobatus ocellatus Kuhl 1823 - Gonzalo Araujo; Rebecca Bateman-John; Jacinta L. Shackleton; Chris Garraway; Nigel Marsh; Daisy Whicheloe; Jade Rosadoni; Aimee Jan; Kohei Saito; Emily Lester (Frontiers in Marine Science, 2024)

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Can freshwater plants and algae act as an effective feed supplement to reduce methane emissions from ruminant livestock? - Rebecca E. Lester; Ashley Macqueen; Emily K. Armstrong; David T. Dodemaide; Georgia K. Dwyer; Thomas S. Mock; Stephanie Payne; Michael Smith; Michaela Storen; Lawrence Webb (Science of The Total Environment, 2024)

COVID-19 and food insecurity in the Blackfeet Tribal Community - Neha A. John-Henderson; Benjamin J. Oosterhoff; Lester R. Johnson; Mary Ellen Lafromboise; Melveena Malatare; Emily Salois (Food Security, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Habitat and Marine Reserve Status Drive Reef Fish Biomass and Functional Diversity in the Largest South Atlantic Coral Reef System (Abrolhos, Brazil) - Fernanda Andreoli Rolim; Tim Langlois; Fábio dos Santos Motta; Guilherme Malagutti de Castro; Emily Lester; Maria Luiza Abieri; Otto Bismarck Fazzano Gadig; Rodrigo Leão de Moura (Frontiers in Marine Science, 2022)
The effects of fishing have been documented across coral reefs worldwide. No-take marine reserves do not only act as a conservation tool but also allow an opportunity to study impacts of fishing, by acting as control sites. In addition, well-planned and well-managed no-take marine reserves (NTRs) provide conservation benefits that are essential to marine biodiversity and ecosystem-based management. The Abrolhos Marine National Park, off the tropical Brazilian coast, protects part of the largest coral reef system in the South Atlantic. To investigate the effects of fishing on reef fish richness, abundance, biomass, and functional diversity of the fish assemblage, we compared sites across two protection levels considering the variation in habitats (Fringing Reefs—Protected; Pinnacles Reefs—Protected; and Coastal Reefs—Open Access), using Baited Remote Underwater Stereo-Video systems (stereo-BRUVs). We adjusted generalized additive mixed models of fish assemblage characteristics with protection levels and environmental variables, such as topographic complexity (mean relief and relief variation), visibility, and benthic cover percentage. Inside NTRs, we found higher total biomass and biomass of fishery target species and carnivores, specifically for the Carcharhinidae (sharks) and Epinephelidae (groupers) families, indicating direct fisheries effects on these groups. In contrast, the ecological parameters of non-target fish were positively correlated with habitat characteristics, including mean relief and variance of relief. Moreover, fish functional diversity was higher within NTRs, demonstrating an even distribution of functional entities. The presence of large mobile predators and the overall higher biomass of carnivores inside the NTR indicate the effect of fishing exclusion. Our results point to the value of NTRs to study the effects of fishing and achieve biodiversity conservation and suggest the importance of using remote sampling methods to assess large mobile predators.

Asymptotic Growth of Whale Sharks Suggests Sex-Specific Life-History Strategies - Mark G. Meekan; Brett M. Taylor; Emily Lester; Luciana C. Ferreira; Ana M. M. Sequeira; Alistair D. M. Dove; Matthew J. Birt; Alex Aspinall; Kim Brooks; Michele Thums (Frontiers in Marine Science, 2020)

Tracing Environmental Sustainability Discourses: An Australia-Asia Seafood Case Study - Coco Cullen-knox; Aysha Fleming; Libby Lester; Emily Ogier (Frontiers in Marine Science, 2020)

Selecting and applying indicators of ecosystem collapse for risk assessments - Jessica A. Rowland; Emily Nicholson; Nicholas J. Murray; David A. Keith; Rebecca E. Lester; Lucie M. Bland (Conservation Biology, 2018)
Ongoing ecosystem degradation and transformation are major threats to biodiversity. Measuring ecosystem change toward collapse relies on monitoring indicators that quantify key ecological processes. Yet little guidance is available on selection and use of indicators for ecosystem risk assessment. We reviewed indicator use in ecological studies of ecosystem collapse in marine pelagic and temperate forest ecosystems. We examined indicator‐selection methods, indicator types (geographic distribution, abiotic, biotic), methods of assessing multiple indicators, and temporal quality of time series. We compared how these factors were applied in the ecological studies with how they were applied in risk assessments by using the International Union for Conservation of Nature's Red List of Ecosystems (RLE), for which indicators are used to estimate risk of ecosystem collapse. Ecological studies and RLE assessments rarely reported how indicators were selected, particularly in terrestrial ecosystems. Few ecological studies and RLE assessments quantified ecosystem change based on all 3 indicator types, and indicators types used differed between marine and terrestrial ecosystems. Several studies used indices or multivariate analyses to assess multiple indicators simultaneously, but RLE assessments did not because as RLE guidelines advise against them. Most studies and RLE assessments used time‐series data that spanned at least 30 years, which increases the probability of reliably detecting change. Limited use of indicator‐selection protocols and infrequent use of all 3 indicator types may hamper accurate detection of change. To improve the value of risk assessments for informing policy and management, we recommend using explicit protocols, including conceptual models, to identify and select indicators; a range of indicators spanning distributional, abiotic, and biotic features; indices and multivariate analyses with extreme care until guidelines are developed; time series with sufficient data to increase ability to accurately diagnose directional change; data from multiple sources to support assessments; and explicitly reporting steps in the assessment process.